Distortion of frontal bones results from cell apoptosis by the mechanical force from the up-migrating eye during metamorphosis in Paralichthys olivaceus. (May 2015) - Sun, Mingyan; Wei, Fen; Li, Hui; Xu, Juan; Chen, Xinye; Gong, Xiaoling; Tian, Yongsheng; Chen, Songlin; Bao, Baolong
Highlights: Distortion of the frontal bones in metamorphic flounders is the result of cell apoptosis via the mitochondrial pathway. Cell apoptosis is induced by the mechanical force transferred from the up-migrating eye via the FAK signaling pathway. The thyroid hormone is unlikely to be involved in the regulation of cell apoptosis in frontal bones. Abstract: Craniofacial remodeling during flatfish metamorphosis, including eye migration, is perhaps the most striking example of asymmetric postembryonic development in the vertebrate world. The asymmetry of the cranium mainly results from distortion of the frontal bones, which depends on eye migration during metamorphosis. However, it is unclear how the up-migrating eye causes distortion of the frontal bones. In this study, we first show that distortion of the frontal bones during metamorphosis in Paralichthys olivaceus is the result of cell apoptosis, rather than cell autophagy or cell proliferation. Secondly, we report that cell apoptosis in the frontal bones is induced by the mechanical force transferred from the up-migrating eye. The mechanical force from the up-migrating eye signals through FAK to downstream molecules that are integrated into the BMP-2 signal pathway. Finally, it is shown that cell apoptosis in the frontal bones is activated by the intrinsic mitochondrial pathway; the extrinsic death receptor is not involved in this process. Moreover, cell apoptosis in frontal bones is not induced directly by thyroid hormones, which are thought to mediate metamorphosis in flatfishes and directly mediate cell apoptosis during amphibian metamorphosis. These findings help identify the major signaling route used during regulation of frontal bone distortion during metamorphosis in flatfish, and indicate that the asymmetry of the cranium, or at least the distortion of frontal bones, is the result of rather than the reason underlying eye migration.